Design and control of the first foldable single-actuator rotary wing micro aerial vehicle. (1st November 2021) - Win, Shane Kyi Hla; Win, Luke Soe Thura; Sufiyan, Danial; Foong, Shaohui
Abstract: The monocopter is a type of micro aerial vehicle largely inspired from the flight of botanical samaras ( Acer palmatum ). A large section of its fuselage forms the single wing where all its useful aerodynamic forces are generated, making it achieve a highly efficient mode of flight. However, compared to a multi-rotor of similar weight, monocopters can be large and cumbersome for transport, mainly due to their large and rigid wing structure. In this work, a monocopter with a foldable, semi-rigid wing is proposed and its resulting flight performance is studied. The wing is non-rigid when not in flight and relies on centrifugal forces to become straightened during flight. The wing construction uses a special technique for its lightweight and semi-rigid design, and together with a purpose-designed autopilot board, the entire craft can be folded into a compact pocketable form factor, decreasing its footprint by 69%. Furthermore, the proposed craft accomplishes a controllable flight in 5 degrees of freedom by using only one thrust unit. It achieves altitude control by regulating the force generated from the thrust unit throughout multiple rotations. Lateral control is achieved by pulsing the thrust unit at specific instances during each cycle of rotation. A closed-loop feedback control is achieved using a motion-captured camera system, where a hybrid proportional stabilizer controller and proportional-integral position controller are applied. Waypoint tracking, trajectory tracking and flight time tests were performed and analyzed. Overall, the vehicle weighs 69 g, achieves a maximum lateral speed of about 2.37 m s −1, an average power draw of 9.78 W and a flight time of 16 min with its semi-rigid wing.